Kerukunan Antarumat Beragama di Kecamatan Denpasar Barat Kota Denpasar Tahun 2005-2021 - Tania Dwi Andita Putri; I Wayan Tagel Eddy; Fransiska Dewi Setiowati Soenaryo (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2022)
This study discusses Inter-religious Harmony in West Denpasar District, Denpasar City, from 2005-2021. West Denpasar is a district with a multicultural society. The population of West Denpasar is the largest among other districts in Denpasar City. The total population of West Denpasar based on the 2020 population census is 188,131 people, includes the number of Hindus, Muslims, Christians, Catholics, Buddhists, and Confucians. The issue of religion is often considered a sensitive issue, therefore maintaining harmony in a multicultural society is not an easy matter. The purpose of this study is to determine the factors that occur inter-religious harmony. Main problem in this study: Why is inter-religious harmony occur in the people's social life in West Denpasar District? The theories used are rational choice, roles, and multiculturalism. This research is qualitative. The method used is the historical method with a comparative religious history approach. Data was collected through literature study, observation, interviews, and documentation. The factors that support the occurrence of interreligious harmony in West Denpasar District, namely menyama braya, the role of the Denpasar City Inter-Religious Harmony Forum, and religious leaders, and rational choices in preventing conflict.